Culture Management (Logos Verlag Berlin, 2021)
"Dr Lukasz Wroblewski's book Culture Management: Strategy and Marketing Aspects clearly recognises that the pressures on the cultural sector in the 21st Century are greater than ever before. Based on robust academic research within a practical industry context, this book addresses all the key issues related to marketing strategy and planning for the cultural industries. It will be an invaluable tool for managers, policy-makers and all those working in the creative and cultural world, and will help them to develop sound strategies for the future." Dr Kim Lehman Tasmanian School of Business and Economics, University of Tasmania "Dr Wroblewski's book explains clearly what has changed to make the use of business models necessary, even in organizations which might have resisted in the past. Globalization has resulted in a population which understands and appreciates art and culture created in other countries. While it might be agreed that this is beneficial for society, it means that cultural arbitrators within a country no longer have the authority to dictate what is accepted as culture. Managers now understand that to gain the support of the public they must explain the benefits of consuming their cultural product." Dr Bonita M. Kolb Professor Emeritus of Lycoming College in Pennsylvania "A thoughtful and penetrating analysis of culture management addressing marketing strategies and cultural institutions. An important `must read' book for those involved in this exciting sector." Prof Adrian Payne University of UNSW Business School, University of New South Wales